Place and Cause of Death in Centenarians: A Population-Based Observational Study in England, 2001 to 2010 - Evans, Catherine J. (Public Library of Science, 2014)
BACKGROUND: Centenarians are a rapidly growing demographic group worldwide, yet their health and social care needs are seldom considered. This study aims to examine trends in place of death and associations for centenarians in England over 10 years to consider policy implications of extreme longevity. METHODS AND FINDINGS: This is a population-based observational study using death registration data linked with area-level indices of multiple deprivations for people aged ≥100 years who died 2001 to 2010 in England, compared with those dying at ages 80-99. We used linear regression to examine the time trends in number of deaths and place of death, and Poisson regression to evaluate factors associated with centenarians’ place of death. The cohort totalled 35,867 people with a median age at death of 101 years (range: 100–115 years). Centenarian deaths increased 56% (95% CI 53.8%–57.4%) in 10 years. Most died in a care home with (26.7%, 95% CI 26.3%–27.2%) or without nursing (34.5%, 95% CI 34.0%–35.0%) or in hospital (27.2%, 95% CI 26.7%–27.6%). The proportion of deaths in nursing homes decreased over 10 years (−0.36% annually, 95% CI −0.63% to −0.09%, p = 0.014), while hospital deaths changed little (0.25% annually, 95% CI −0.06% to 0.57%, p = 0.09). Dying with frailty was common with “old age” stated in 75.6% of death certifications. Centenarians were more likely to die of pneumonia (e.g., 17.7% [95% CI 17.3%–18.1%] versus 6.0% [5.9%–6.0%] for those aged 80–84 years) and old age/frailty (28.1% [27.6%–28.5%] versus 0.9% [0.9%–0.9%] for those aged 80–84 years) and less likely to die of cancer (4.4% [4.2%–4.6%] versus 24.5% [24.6%–25.4%] for those aged 80–84 years) and ischemic heart disease (8.6% [8.3%–8.9%] versus 19.0% [18.9%–19.0%] for those aged 80–84 years) than were younger elderly patients. More care home beds available per 1,000 population were associated with fewer deaths in hospital (PR 0.98, 95% CI 0.98–0.99, p<0.001). CONCLUSIONS: Centenarians are more likely to have causes of death certified as pneumonia and frailty and less likely to have causes of death of cancer or ischemic heart disease, compared with younger elderly patients. To reduce reliance on hospital care at the end of life requires recognition of centenarians’ increased likelihood to “acute” decline, notably from pneumonia, and wider provision of anticipatory care to enable people to remain in their usual residence, and increasing care home bed capacity. Please see later in the article for the Editors' Summary